Efficacy and safety of ixekizumab in a randomized, double‐blinded, placebo‐controlled phase IIIb study of patients with moderate‐to‐severe genital psoriasis. (1st October 2018) - Ryan, C.; Menter, A.; Guenther, L.; Blauvelt, A.; Bissonnette, R.; Meeuwis, K.; Sullivan, J.; Cather, J.C.; Yosipovitch, G.; Gottlieb, A.B.; Merola, J.F.; Callis Duffin, K.; et al.
Summary: Background: Genital psoriasis (GenPs) is a common, debilitating and difficult‐to‐treat manifestation of plaque psoriasis. However, few controlled, interventional studies of GenPs exist. Objectives: To determine the efficacy of ixekizumab vs. placebo in patients with moderate‐to‐severe GenPs with ≥ 1% involved body surface area (BSA). Methods: Patients with moderate‐to‐severe GenPs, defined as a baseline static Physician's Global Assessment of Genitalia (sPGA‐G) score of ≥ 3, with BSA ≥ 1% were randomized 1 : 1 to receive placebo ( n = 74) or the recommended dosing of ixekizumab ( n = 75). Major outcomes included the percentage of patients achieving 0 or 1 scores on the sPGA‐G (primary end point), overall sPGA, GenPs Sexual Frequency Questionnaire (GenPs‐SFQ) item 2, and ≥ 3‐point improvement from baseline on the GenPs itch numerical rating scale. Results: At week 12, ixekizumab was superior to placebo for sPGA‐G 0/1 (73% vs. 8%, P < 0·001), overall sPGA 0/1 (73% vs. 3%, P < 0·001), GenPs‐SFQ item 2 score of 0 or 1 (78% vs. 21%, P < 0·001) and genital itch (60% vs. 8%, P < 0·001). No candidiasis was reported, no deaths occurred and one (1%) serious adverse event was reported in a patient receiving placebo. Conclusions: Ixekizumab was superior to placebo for the treatment of moderate‐to‐severe GenPs with BSA ≥ 1%. The safety profile of ixekizumab was consistent with previous studies in moderate‐to‐severe plaque psoriasis.